2015
DOI: 10.1038/nn.4102
|View full text |Cite|
|
Sign up to set email alerts
|

Regulating anxiety with extrasynaptic inhibition

Abstract: Aversive experiences can lead to complex behavioral adaptations including increased levels of anxiety and fear generalization. The neuronal mechanisms underlying such maladaptive behavioral changes, however, are poorly understood. Here, using a combination of behavioral, physiological and optogenetic approaches in mouse, we identify a specific subpopulation of central amygdala neurons expressing protein kinase C δ (PKCδ) as key elements of the neuronal circuitry controlling anxiety. Moreover, we show that aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
183
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(194 citation statements)
references
References 34 publications
9
183
2
Order By: Relevance
“…The study concluded that extrasynaptic α5-GABA A Rs in CEA PKCδ + neurons control anxiety. Taken together, our results and the study by Botta et al (2015) suggest the possibility that the anxiolytic-like effects of the specific modulation of α5-GABA A Rs reported here may be due, at least in part, to the positive modulation of the α5-GABA A Rs in this specific neuronal population.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The study concluded that extrasynaptic α5-GABA A Rs in CEA PKCδ + neurons control anxiety. Taken together, our results and the study by Botta et al (2015) suggest the possibility that the anxiolytic-like effects of the specific modulation of α5-GABA A Rs reported here may be due, at least in part, to the positive modulation of the α5-GABA A Rs in this specific neuronal population.…”
Section: Discussionsupporting
confidence: 77%
“…As the ventral hippocampus has been linked to emotion and stress, whereas the dorsal hippocampus has been linked primarily to cognitive functions (Fanselow and Dong, 2010), α5-GABA A Rs in the ventral hippocampus may be involved in anxiolysis. Furthermore, a recent study showed that conditional genetic deletion of α5 in the central nucleus of the amygdala (CEA) leads to anxiogenic-like effects and increased fear generalization (Botta et al, 2015). The study concluded that extrasynaptic α5-GABA A Rs in CEA PKCδ + neurons control anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible candidate is GABA, the most common inhibitory neurotransmitter in our nervous system (Steighart, 1995). Animal studies suggest that GABA plays an important role in learning (Botta et al, 2015;Jovasevic et al, 2015). Importantly, there is evidence that prediction error signalling during learning seems to involve GABA (Kim et al, 1998).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, the relations are not straightforward; for instance, high activity at α1-GABAA-Rs induces sedation and contributes to amnesia, but the same receptor subtype is also implicated in cognition by co-localizing with α5 and γ2 subunits [15]. The BZ anxiolytic properties are mediated predominantly by α2-GABAA-Rs [16] and also by α5-GABAA-Rs [17, 18]. Selective activity at α5-GABAA-Rs has also been suggested to play a critical role in alleviating “behavioral emotionality” (anxiety and depressive-like behaviors) in a mouse model of depression (using chronic stress in mice [19]) or cognitive dysfunctions in mouse models of schizophrenia [20] or in old rats [21].…”
Section: Introductionmentioning
confidence: 99%